Effect of Hypoxic Ischaemic Encephalopathy on Coagulation Profile in Neonates in a Tertiary Care Center, Agra- A Prospective Clinical Study - Payal Mittal; Shehraz Firoz; Digvijay Ghangas; Sonia Bhatt (JCDR Research and Publications Pvt. Ltd., 2023)
Introduction: Perinatal asphyxia is very common in developing countries. Coagulopathy occurs as a part of spectrum of multiorgan dysfunction following hypoxic insult. In asphyxiated neonate, bleeding due to coagulation abnormality is common and potentially life threatening. There are very few studies done on coagulation profile with perinatal asphyxia in last few decades. Aim: To evaluate the coagulation profile in neonates with hypoxic ischaemic encephalopathy in a tertiary care center, Agra. Materials and Methods: This was a prospective clinical study undertaken in Neonatal Intensive Care Unit (NICU) FH Medical College Agra, a tertiary care center catering rural and urban population. Total 60 neonates admitted with history of birth asphyxia between January 2022 to June 2022 were enrolled. Neonates were classified into Hypoxic Ischaemic Encephalopathy (HIE) stage 1, 2 and 3 (according to Sarnat and Sarnat staging). Parameters such as Prothrombin Time (PT)/ International Normalised Ratio (INR) and platelet count was analysed. For describing continuous variables means and standard deviations and for comparison Analysis of Variance (ANOVA) test and Chi-square test were used. Results: In this study, total 60 neonates were enrolled. Out of these 43 (71.61%) were male and 17 (28.33%) female. Highest number of cases 34 (56.7%) were from HIE stage 3 followed by 22 (36.7%) HIE stage 2 and 4 (6.7%) from HIE stage 1. Among them 14 newborns with HIE stage 3 were died. PT and INR was significantly deranged in HIE stage 3 and 2 (p-value <0.05). HIE stage 3 has highest mortality and morbidity. Platelet count were normal in HIE stage 1 followed by decreased in HIE stage 2 and 3 and also statistically significant. Conclusion: Coagulation derangement is very common in babies with HIE and evident before clinical bleeding and this derangement is associated with poor outcome. Hence, timely intervention and appropriate management can improve the clinical outcome.